Application of MEC-based positioning technology in the Internet of vehicles - Bo GU; Ting AO (Dianxin kexue)
Positioning is not only the cornerstone of ensuring the safe driving of vehicles, but also the foundation of many location-related services.The development and application of the positioning technology have greatly affected the development prospects of the Internet of vehicles.Mobile edge computing can migrate intensive computing tasks to the edge of the network adjacent to the car or roadside.By sinking the computing power to the edge of the network, mobile edge computing can offload the load of network transmission, save the transmission bandwidth, and support Internet of vehicles applications powerfully.It was aimed to study the integration of MEC and IoV positioning technology, and form the overall architecture of MEC-based positioning technology by analyzing the application scenarios and integration requirements of MEC integrated positioning technology in IoV.At the same time, the opportunities and challenges of the architecture were further analyzed to provide an important reference for the subsequent standardization of MEC-based positioning technology and the application in the Internet of vehicles.